The use of palm oil in aquaculture feeds for salmonid species - Ng, Wing–Keong; Tocher, Douglas R; Bell, J Gordon (European Journal of Lipid Science and Technology, 2007)
In this overview, our current knowledge and research being conducted on the use of palm oil in the commercial feeds for cold-water salmonid species such as Atlantic salmon and rainbow trout will be highlighted. Salmonids have a high requirement for lipid as a source of energy and n-3 polyunsaturated fatty acids (PUFA) to maintain membrane fluidity in a cold water environment. The culture of salmonid fishes has traditionally depended on marine fish oils for this purpose but with limited supplies and the rapid increase in salmon production, alternatives to fish oils must be investigated. Research has shown that crude palm oil can be used to replace 100% of added fish oils in salmonid diets without compromising growth performance and feed utilization efficiency despite reductions in lipid and fatty acid digestibilities that occurs during low water temperatures in the winter rearing season. Fatty acid desaturation and elongation activities increased with increasing dietary palm oil and to a certain extent, decreasing water temperatures. The effects of palm oil on fish health requires further research but the use of this more saturated vegetable oil may reduce oxidative stress in fish thereby reducing pathological conditions associated with this physiological state. It is generally known that fish fillet fatty acid composition directly reflects that of the dietary oil used. Extrapolating from work done with other vegetable oils, the supply of beneficial n-3 (omega-3) PUFA in salmon fillets to the human consumer can be maintained by using a “wash-out” feeding strategy just prior to harvesting despite significant reductions in these fatty acids when high levels of dietary palm oil are used to feed fish. The use of palm oil can also add additional benefits to fillet quality and health benefits to the consumer due to the potential bioaccumulation of tocopherols and tocotrienols in salmon flesh and minimizing the deposition of undersirable fatty acids such as 18:2(n-6). Fillet texture and color were not affected by ...